Advances in the Application of Radionuclide-Labeled HER2 Affibody for the Diagnosis and Treatment of Ovarian Cancer - Hu, Xianwen; Li, Dandan; Fu, Yujie; Zheng, Jiashen; Feng, Zelong; Cai, Jiong; Wang, Pan (Frontiers in Oncology, 2022)
Human epidermal growth factor receptor 2 (HER2) is a highly expressed tumor marker in epithelial ovarian cancer, and its overexpression is considered to be a potential factor of poor prognosis. Therefore, monitoring the expression of HER2 receptor in tumor tissue provides favorable conditions for accurate localization, diagnosis, targeted therapy, and prognosis evaluation of cancer foci. Affibody has the advantages of high affinity, small molecular weight, and stable biochemical properties. The molecular probes of radionuclide-labeled HER2 affibody have recently shown broad application prospects in the diagnosis and treatment of ovarian cancer; the aim is to introduce radionuclides into the cancer foci, display systemic lesions, and kill tumor cells through the radioactivity of the radionuclides. This process seamlessly integrates the diagnosis and treatment of ovarian cancer. Current fresearch and development of new molecular probes of radionuclide-labeled HER2 affibody should focus on overcoming the deficiencies of non-specific uptake in the kidney, bone marrow, liver, and gastrointestinal tract, and to reduce the background of the image to improve image quality. By modifying the amino acid sequence, changing the hydrophilicity, surface charge, and lipid solubility of the affibody molecule, and by using different radionuclides, chelating agents, and labeling conditions to optimize the labeling method of molecular probes, the specific uptake of molecular probes at tumor sites will be improved, while reducing radioactive retention in non-target organs and obtaining the best target/non-target value. These measures will enable the clinical use of radionuclide-labeled HER2 affibody molecular probes as soon as possible, providing a new clinical path for tumor-specific diagnosis, targeted therapy, and efficacy evaluation. The purpose of this review is to describe the application of radionuclide-labeled HER2 affibody in the imaging and treatment of ovarian cancer, including its potential clinical value and dilemmas.